Vulnerability of mineral-associated soil organic carbon to climate across global drylands - Díaz-Martínez, Paloma (2024)
Mineral-associated organic carbon (MAOC) constitutes a major fraction of global soil carbon and is assumed less sensitive to climate than particulate organic carbon (POC) due to protection by minerals. Despite its importance for long-term carbon storage, the response of MAOC to changing climates in drylands, which cover more than 40% of the global land area, remains unexplored. Here we assess topsoil organic carbon fractions across global drylands using a standardized field survey in 326 plots from 25 countries and 6 continents. We find that soil biogeochemistry explained the majority of variation in both MAOC and POC. Both carbon fractions decreased with increases in mean annual temperature and reductions in precipitation, with MAOC responding similarly to POC. Therefore, our results suggest that ongoing climate warming and aridification may result in unforeseen carbon losses across global drylands, and that the protective role of minerals may not dampen these effects.